2012
DOI: 10.1007/s10310-011-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Seedlings of a native shrub can establish under forests dominated by an alien tree, Casuarina equisetifolia, on subtropical oceanic islands

Abstract: We investigated the effects of litter accumulation by an alien tree, Casuarina equisetifolia, on the germination and seedling establishment of Rhaphiolepis wrightiana, a shrub native to the Ogasawara (Bonin) Islands, in the northwestern Pacific Ocean, in a field experiment. We compared the emergence of seedlings in forests dominated by C. equisetifolia with that in native forests, with and without litter removal. More than 75% of seedlings emerged during a year except at the C. equisetifolia sites with litter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This is the main reason why the absence of litter also reduced seedling emergence of native species in the field. Similarly, Hata et al (2012) observed that removal of litter reduced seedling establishment of a native shrub in an area invaded by C. equisetifolia.…”
Section: Seed Dispersal May Limit Invasion and Increase Native Re-colonizationmentioning
confidence: 86%
See 2 more Smart Citations
“…This is the main reason why the absence of litter also reduced seedling emergence of native species in the field. Similarly, Hata et al (2012) observed that removal of litter reduced seedling establishment of a native shrub in an area invaded by C. equisetifolia.…”
Section: Seed Dispersal May Limit Invasion and Increase Native Re-colonizationmentioning
confidence: 86%
“…The likelihood of a dispersed M. obtusifolia seed becoming an established seedling was almost five times higher in the Casuarina stand below litter than inside vegetation patches. This helps to drive recolonization of native shrubs in areas invaded by this alien species (Hata et al 2012). In addition, seedlings of M. obtusifolia survived longer than 24 months in both vegetation types, probably due to seedling morphology.…”
Section: Seed Dispersal May Limit Invasion and Increase Native Re-colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The density and size of L. leucocephala seedlings in the seed sowing experiment confirmed that this species can invade and dominate forest gaps following the death of C. equisetifolia if there are sufficient amounts of dispersed seeds. In nature, there are few L. leucocephala seedlings and saplings in the understory of forests dominated by C. equisetifolia (Hata et al 2009), probably because L. leucocephala cannot invade undisturbed forests with closed canopies (Yamamura et al 1999). L. leucocephala seeds are supplied by both mature trees and the soil seed bank.…”
Section: Impacts Of Secondary Leucaena Leucocephala Invasion After Co...mentioning
confidence: 99%
“…Both species have aggressively invaded and caused serious problems in tropical and subtropical ecosystems, especially on islands (Weber 2017). On the Ogasawara Islands, C. equisetifolia dominates secondary forests, where there are fewer seedlings and saplings of native trees (Hata et al 2009) due to the inhibition of seed germination and initial growth of native tree seedlings (Hata et al 2010a). Therefore, C. equisetifolia has been controlled on these islands to restore native forest ecosystems (Japan Ministry of the Environment 2011).…”
Section: Introductionmentioning
confidence: 99%